ABUSE OF DOMINANT POSITION BY MARGIN SQUEEZE IN COMPETITION LAW OF THE EUROPEAN UNION - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Abstract: Margin squeeze occurs when vertically integrated undertaking, which is dominant on the upstream market, charges a price for the product on the upstream market which, compared to the price it charges on the downstream market, does not allow even an equally efficient competitor to trade profitably in the downstream market on a lasting basis.The subject of the analysis in the paper is the abuse of a dominant position by margin squeeze in the competition law of the European Union. The author will present and analyze relevant competition rules in the European Union, the practice of the Court of Justice of the European Union and the European Commission, as well as views expressed in the doctrine, in order to answer whether margin squeeze is an independent type of abuse of dominant position and what conditions are relevant for legal analysis of margin squeeze.
Keywords: Abuse of dominant position, exclusionary abuse, margin squeeze, refusal to supply.